Bridging the Gap: Human Resource Management Strategies in Romania's Evolving Labor Market within the European Union Framework. Study Case in Bihor County, Romania. - Delia-Georgeta BEKESI; Zsolt-Botond BOTTYAN (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This study examines the role of human resource management (HRM) practices in addressing labor market challenges in Romania, a relatively new member of the European Union (EU). Focusing on Bihor County, the research investigates how Romanian employers adapt their HRM strategies to navigate labor shortages and align with EU competitiveness standards. Through a quantitative analysis of 254 private sector employers, the study explores the interplay between post-communist entrepreneurial culture, evolving HRM practices, and EU-driven economic objectives. Findings reveal a persistent parochial management approach, with employers reluctant to engage professional recruitment services or explore international labor markets. The research identifies a significant mismatch between employer demands and available skills, particularly in vocational and technical fields. While employers recognize the value of workplace training, there is less emphasis on other retention strategies such as competitive compensation or work-life balance initiatives. The study highlights the need for closer collaboration between educational institutions and employers to align training programs with market needs. It also underscores the importance of developing more sophisticated HRM strategies to address ongoing labor shortages and enhance Romania's competitiveness within the EU. This research contributes to the understanding of HRM's role in bridging the gap between Romania's economic potential and its current performance within the EU framework.